Say you'll be mine : a novel - Kumar, Naina (Dell, 2024)
"My Best Friend's Wedding meets Never Have I Ever in this utterly charming, heart-stealing debut romance about two completely different people who get engaged under false pretenses. "I couldn't put down this page-turner . . . A warm, smart, sexy, and absolutely charming debut." -Colleen Hoover When Seth, Meghna's one-who-got-away writing partner and best friend, asks Meghna Raman to be the "best man" for his last-minute wedding, Meghna is determined to move on, even if it means telling her mother she's finally open to an arranged marriage. Since she-a theater teacher and an aspiring playwright-won't fulfill her parents' dreams of becoming an engineer, she might as well marry one. Grumpy, handsome, no-nonsense engineer Karthik Murthy has seen enough of his parents' relationship to know marriage is not for him. He only agreed to his mom's matchmaking attempts to make her happy, never dreaming he'd meet someone as vibrant as Meghna. Though he can't offer a real marriage, a fake engagement could help him avoid the absurd number of arranged set-ups his mother has planned for the next year. Thinking a faux fiancé will dampen the sting of her ex's wedding festivities, Meghna agrees to team up with Karthik until the wedding ends. But as they find common ground and their undeniable chemistry takes shape, their expectations and insecurities threaten to risk something that's become a lot more real than they had hoped"--